(untitled) (World Economics and Finance Bulletin, 2023)
The quantitative easing policy is an unconventional monetary policy, which was followed by countries that suffered from economic deficits during certain periods. Direct monetary policies were not able to solve these deficits, which were represented by reaching that the basic interest rate reached zero and was unable to move credit in those countries so this forced those countries to use the policy of quantitative easing to get out of those deflations, especially Japan and the United States of America and other countries such as Britain and the European Union ... so has been used the phrase (quantitative easing) was used to refer to a shift from a focus on using quantitative variables, especially Purchasing government or banking securities to increase liquidity that brings commercial banks more amounts prepared for lending and at a zero or close to zero interest rate. Through the use of this policy, By using this policy Japan has been able to encourage borrowing and direct investors towards establishing new projects and thus achieving a certain level of economic recovery in Japan, The policy continued to be used to break out of the downturn in the global economy after the 2008 mortgage crisis, through a set of different measures taken by the central banks in those countries to increase the rate of economic growth in those countries